Recent Development of VUV-Based Processes for Air Pollutant Degradation - Huang, Haibao; Lu, Haoxian; Huang, Huiling; Wang, Lei; Zhang, Jieni; Leung, Dennis Y. C. (Frontiers in Environmental Science, 2016)
As air pollution become more and more serious nowadays, it is essential to find out a way to efficiently degrade the air pollutants. Vacuum ultraviolet (VUV)-based processes are an emerging and promising technologies for environmental remediation such as air cleaning, wastewater treatment and air/water disinfection. With VUV irradiation, photolysis, photocatalyst is and ozone-assisted oxidation are involved at the same time, resulting in the fast degradation of air pollutants because of their strong oxidizing capacity. The mechanisms of how the oxidants are produced and reacted are discussed in this review. This paper mainly focuses on the three VUV-based oxidation processes including VUV photolysis, VUV combined with ozone-assisted oxidation and VUV-PCO with emphasis on their mechanisms and applications. Also, the outlooks of these processes are outlined in this paper.